Museums and Tourism: Reengineering The Role Of Museums In Malaysia’s Cultural Heritage Tourism - ShawHong SER (Bina Nusantara University, 2020)
Since 2013, cultural heritage tourism has been identified as a new segment to be developed by the Malaysia Tourism Promotion Board (MTPB). Today, the sector has undergone rapid growth and have a great impact on Malaysia’s tourism industry, as well as bring prospects for developing museum tourism in Malaysia. In this paper, to respond on the research scholarly interest in cultural management. The researcher discusses the roles of the museum to sustainable cultural heritage tourism growth with a special focus on challenges faces by Malaysia’s museum sector in developing museum tourism. Over the years, many researches have been done, and still researching by scholars on the need for cultural resource management placing focus on the role they take towards cultural economic development. The purpose of this research, among others, is to explore how museums in Malaysia could be more effectively utilized for museum tourism and to make suggestions for better utilization of the museum sector for cultural heritage tourism development. It is hoped that this paper will provide insights into an understanding of cultural heritage tourism in Malaysia with an emphasis on crisis and opportunity in developing museum tourism.